Medical ethics and profit motivated medical practice - the dilemma of a modern day private health practitioner. - Obert, Sifile; Mutsa, Mhangara; Desderio, Chavunduka; Brighton, Bhebhe Thomas (Archives of Business Research, 2018)
The rapid emergence of for-profit health care organizations over the past few years poses critical questions on the ethics of health care delivery. The study explores the ethical implications of commodification of health care service as it relates to the healing relationship between the professionals and their patients. A cross-sectional study of for-profit health practitioners in Harare Metropolitan Province, Zimbabwe was done from a representative sample size which was randomly selected from the practitioners register. Respondents answered self-administered questionnaires and key informant interviews. Data was analyzed using Epi Info Version 7, to generate descriptive and inferential statistics. A significant proportion of for-profit medical practitioners are not practicing or adhering to good ethical practices but preferring alternatives which generate income. Medical ethics should be viewed as dynamic, situational and circumstantial. The study concludes that unregulated commodification of health care services, negatively affects the healing relationship between the professionals and their patients due to lack of trust which is the fundamental backbone of the relationship. The study recommends that regulators of medical practice, Health Professions Authority and Medical and Dental Practitioners Council, should regularly review the ethical conducts standards for practitioners since they are dynamic and not to rigidly codify ethics, as they prevent better human relations and adjustments.